Political awareness and involvement of college of arts and sciences students of Laguna State Polytechnic University - Jherwin P. Hermosa (Northern Negros State College of Science and Technology (NONESCOST), 2021)
The study sought to determine the level of Political Awareness and Involvement of College of Arts and Sciences Students of Laguna State Polytechnic University. The quantitative and descriptive-correlational method was employed using a self-made questionnaire with 60 respondents. To determine the relationship of political awareness and involvement of the respondents, Pearson correlation analysis was used. The research revealed that the respondents' political awareness such as public policies, political leaders, and political issues is high. On the other hand, the respondents' political involvement pertaining to voting, involvement in public discussions, and political activism are high. It was revealed that the awareness of political leaders is significantly correlated to voting and involvement in public discussion, while the awareness of political issues is significantly related to involvement in voting. While there is no relationship with the remaining variables.